2015
DOI: 10.1530/erc-14-0269
|View full text |Cite
|
Sign up to set email alerts
|

CD74 expression and its therapeutic potential in thyroid carcinoma

Abstract: CD74, the invariant chain of major histocompatibility complex class II, is also a receptor for macrophage migration inhibitory factor (MIF). CD74 and MIF have been associated with tumor progression and metastasis in hematologic and solid tumors. In this study, we found that 60 and 65% of papillary thyroid cancers were positive for CD74 and MIF immunohistochemical staining respectively. Anaplastic thyroid cancer was negative for MIF, but mostly positive for CD74 expression. Normal thyroid tissue and follicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 42 publications
2
34
1
Order By: Relevance
“…Postoperative KPS scores have superior predictive capabilities for overall survival in glioblastoma patients and should replace preoperative KPS scores when estimating prognosis (20) . Similar to previous association studies of CD74 expression and survival in other cancers, KaplanMeier overall survival analyses for CD74 expression levels revealed a significant association between high CD74 expression and poorer prognosis (log-rank test, P = 0.05) (7,10,11) . Furthermore, our data confirmed worst prognosis for high-grade glioblastoma with high levels of CD74 expression.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Postoperative KPS scores have superior predictive capabilities for overall survival in glioblastoma patients and should replace preoperative KPS scores when estimating prognosis (20) . Similar to previous association studies of CD74 expression and survival in other cancers, KaplanMeier overall survival analyses for CD74 expression levels revealed a significant association between high CD74 expression and poorer prognosis (log-rank test, P = 0.05) (7,10,11) . Furthermore, our data confirmed worst prognosis for high-grade glioblastoma with high levels of CD74 expression.…”
Section: Discussionsupporting
confidence: 83%
“…However, our data suggest that CD74 expression alone is not an independent marker for poor prognosis and it requires the expression of MIF for tumor pathogenesis, as previously reported in other studies (4,7,16,17,18) . Although we did not perform co-localization staining for MIF-CD74 in this retrospective study, evidence of MIF and CD74 co-localization reported in several other studies (7,8,9,10,11,12,13,14) .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…By immunohistochemistry, CD74 staining was observed to be co-localized with CD44 in some epithelial cells lining the BC in ADR-injured glomeruli, suggesting a role for CD74 expression in PEC activation. Although recent studies have suggested possible roles for the CD74-CD44 receptor complex and its ligand MIF in tumor cell proliferation [13,14,15,16], their roles in kidney diseases have not been elucidated; therefore, we attempted to evaluate CD74 expression in PEC activation and performed comparative analysis of CD74 and other PEC markers.…”
Section: Discussionmentioning
confidence: 99%
“…CD74 acts as a cell membrane receptor for the macrophage migration inhibitory factor (MIF), and the formation of the CD44-CD74 complex initiates the signaling pathway triggered by MIF in macrophages [9] and B cells [10,11,12], inducing cell proliferation and survival. Moreover, several studies suggested a role for CD74 expression in the progression of thyroid, breast, pancreatic, skin and gastrointestinal tract cancers [13,14,15,16]; however, only a few studies were conducted to evaluate the role of CD74 expression and that of CD74-CD44 complex in kidney diseases [17,18]. …”
Section: Introductionmentioning
confidence: 99%